Commodification: Rural Tourism Development in Traditional Village of Nagari Sijunjung - Ermayanti; Indrizal, Edi; Irwandi, Ade; Erwin; Hairul Anwar (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
This paper shows the commodification process that occurs in Kampung Adat Sijunjung to support the development of rural tourism. The commodification process can be seen in the use of Rumah Gadang as a homestay place for guests. Rumah Gadang for the Minangkabau people is not just a place to live but a space and cultural symbol. So that if it is used as a homestay it will cause a dilemma, on the one hand Rumah Gadang needs to be maintained as a distinctive Minangkabau cultural monument and on the other hand the tourism aspect can have an economic impact on the people of Sijunjung. The dualism of Rumah Gadang as a cultural product and tourism product is what results in commodification to develop tourism in rural areas. The method used was thorough observation of Rumah Gadang and interviewing 15 residents and Ninik Mamak (traditional ruler) as members of the tribe that owns Rumah Gadang. In addition, Rumah Gadang continues to function as a place and space for social and cultural activities of the Sijunjung community. So that the values and norms that exist in Rumah Gadang as a symbol of Minangkabau culture continue to run and through homestays, the Sijunjung community can obtain additional economic benefits from the tourism sector.